(3TQM GdJaJGRGfj Ydi JdNjU GdeYGfj hGdHjGf, GdeYQha HGdeNJUQs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, J (B793(3g` (B1390(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO gh GdKfGA HGddSGf Ydi bUO GdJYXje ShGA JYdb HGdfYeI Ch HYVgG hGdTcQ aYd eHfj Yf JYXje GdefYe dchfg efYeG ShGA cGf HGddSGf Ch HGdLfGfs
(3BNQgG (B:s
(3BNQgG(B: (3hGdbhGYO GdePchQI aj Gdafhf GdKdGKI GdJj dG jecf GdGWdGY Ydi JaGUjdgG hJaGQjbgG EdG HYdGe GdZjhH aEfg jXgQ HJPcQgG Cf cdGeg PGdc hbhY ehbYg HGdfXQ Edi ebJVjGJ GdCMhGd hEf cdG ef GdShQ HGdfSHI Edi GdeYfi GdPj jJVefg eTJed Ydi GdaGJMI (B... (3hefWhjI Ydis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B/ (3L (B7: 219s
(3cTa GdXfhf, L (B1: 474s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs